Cancer-related cognitive impairment in older adults. Issue 1 (March 2017) - Edelstein, Andrew; Pergolizzi, Denise; Alici, Yesne
Abstract : Purpose of review: Cancer, aging, and cognition form a complicated interface that can challenge patients, caretakers, and healthcare professionals. Although the typical aging process allows for compensatory mechanisms to help maintain daily functioning, cancer and cancer treatments can remove the fail-safes and exacerbate cognitive decline. As a result, older cancer patients can experience increased morbidity and mortality. The goal of this article is to provide additional assessment strategies, diagnostic considerations, and treatment options for providers taking care of this growing population. Recent findings: In this review, we will discuss current areas of research with regard to epidemiology and our current understanding of cancer-related cognitive impairment in the older patient, while reinforcing the importance of the Comprehensive Geriatric Assessment in assessment, prognosis, and treatment guidance. Summary: Although cognitive impairment in the older cancer patient may be an increasing cause of concern with several gaps in research, there are opportunities to take a methodical treatment approach.